A dual-targeting strategy for enhanced drug delivery and synergistic therapy based on thermosensitive nanoparticles. Issue 11 (24th July 2018) - Wang, Mingxin; You, Chaoqun; Gao, Zhiguo; Wu, Hongshuai; Sun, Baiwang; Zhu, Xiaoli; Chen, Renjie
Abstract: The functionalized nanoparticles have been widely studied and reported as carriers of drug transport recently. Furthermore, many groups have focused more on developing novel and efficient treatment methods, such as photodynamic therapy and photothermal therapy, since both therapies have shown inspiring potential in the application of antitumor. The mentioned treatments exhibited the superiority of cooperative manner and showed the ability to compensate for the adverse effects caused by conventional monotherapy in proposed strategies. In view of the above descriptions, we formulated a thermosensitive drug delivery system, which achieved the enhanced delivery of cisplatin and two photosensitizers (ICG and Ce6) by dual-targeting traction. Drawing on the thin film hydration method, cisplatin and photosensitizers were encapsulated inside nanoparticles. Meanwhile, the targeting peptide cRGD and targeting molecule folate can be modified on the surface of nanoparticles to realize the active identification of tumor cells. The measurements of dynamic light scattering showed that the prepared nanoparticles had an ideal dispersibility and uniform particle size of 102.6 nm. On the basis of the results observed from confocal laser scanning microscope, the modified nanoparticles were more efficient endocytosed by MCF-7 cells as a contrast to SGC-7901 cells. Photothermal conversion-triggered drug release and photo-therapies produced a significant apoptosis rate of 85.9% on MCF-7 cells. The distinguished results made it believed that the formulated delivery system had conducted great efforts and innovations for the realization of concise collaboration and provided a promising strategy for the treatment of breast cancer.